Ellipsoid Approximation versus 3D Rotational Angiography in the Volumetric Assessment of Intracranial Aneurysms - Piotin, M.; Daghman, B.; Mounayer, C.; Spelle, L.; Moret, J. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: The purpose of this study was to compare the volumetric results of intracranial aneurysms obtained by calculation of the volume of an ellipsoid with those obtained with 3D rotational angiography (3D-RA).METHODS: First, the precision of 3D-RA in the assessment of volumetric measurement of intracranial aneurysm had to be established. The 3D-RA gave an overestimation of 4% to 5.5% of the actual volume of a spherical object. Then, 484 consecutive human intracranial aneurysms were studied with 3D-RA, allowing the determination of their volume. In the meantime, aneurysm dimensions (height and width) were measured on the 3D pictures generated by the 3D-RA. The aneurysm volumes were calculated (Vcalc) by considering the aneurysm shape to be ellipsoidal.RESULTS: The calculated aneurysm volume (Vcalc) overestimated by 15 ± 38% the volume given by 3D-RA. Taking into account a 10% margin of error, 227 (47%) aneurysms were overestimated by 44 ± 34%, whereas 113 (23%) aneurysms were underestimated by 25 ± 12%. Only 144 (30%) aneurysms had calculated and 3D-RA results within the limits of 10% of discrepancy. Concordance was good for pericallosal and basilar tip aneurysms (mean overestimation of 6 ± 22% and 8 ± 27%, respectively). Conversely, there was a high discrepancy between calculated and 3D-RA results for posterior communicating artery aneurysms (mean overestimation of 22 ± 44%).CONCLUSION: The calculation of the volume based on aneurysm dimensions is relatively accurate for pericallosal and basilar tip aneurysms, probably owing to their spherical or elliptic shape. Conversely, this formula is not adequate for irregularly shaped lesions, such as posterior communicating aneurysms.